THE EUROPEAN UNION NORTH–SOUTH DIVIDE AND THE FUTURE OF THE EURO - M. M. Khmelnitskiy (MGIMO University Press, 2013)
The debt crisis is continuing in the eurozone, putting on agenda a question about the future of the euro and European integration. In 2012 none of the Southern European states could achieve the EU average GDP per capita. If the Greece’s GDP reduces in 2013 by 4,5% as expected, the Government will hardly fulfill its objective to achieve the growth in 2014. Moreover, Europe has become divided into two macroregions: poor South and prosperous North. The differences between them seem to be predefined because of specific EU policy during the creation of the economic union and when the euro was being introduced; these differences are one of the main causes of the crisis. Inspite of the fact that the Southern countries are still in economic decline, the Northern counties are insisting on austerity measures without any plans to reindustrialize Greece, Spain and Portugal in perspective. The «troika» of lenders saved the eurozone on account of multi-billion aid but it is still nothing done to cope with existing political and economic contradictions such as: trade deficit between «North» and «South», dependence on exports, specific international specialization of Greece, Spain and other countries. Three scenarios can be worked out to foresee the situation in the EU: optimistic, pessimistic and neutral. The pessimistic scenario was widely spread in the expert community. However, it is not that popular at the moment. A strong political will is needed to realize the optimistic scenario in the EU, mainly that of Germany and the Netherlands. At the moment the occasions meet the neutral scenario. It means that the euro area still exists but the coming years can become a «lost decade».